Comparative study between noninvasive techniques for diagnosis of helicobacter pylori in patients with dyspepsia - Seham K.A Khirala; Omnia A El-dydamoni; Soad E Abdel Rehim; Mervat M El missiry (Wolters Kluwer Medknow Publications, 2021)
Background and Aim Helicobacter pylori (H. pylori) is a common etiology for infection-related cancers and represents 5.5% of global cancer burden that increases the need for more sensitive noninvasive diagnostic techniques. The aim was to evaluate the role of saliva and stool samples in the diagnosis of H. pylori infection to replace invasive techniques and to compare between three noninvasive diagnostic tests: salivary culture, PCR, and rapid stool antigen test (RSAT). Patients and methods The study was conducted on 45 patients with dyspepsia and 45 healthy participants as a control. Saliva and stool samples were taken from all groups and subjected to culture, PCR for detection of 16SrRNA gene of H. pylori, and RSAT to detect H. pylori. Gastric biopsy samples were taken for H. pylori culture, rapid urea test, and histopathology from 20 patients. Results A total of 15.6% specimens were positive by salivary culture in patients' group and 2.2% specimens were positive in the control group. About 31% were positive by salivary PCR in patients' group and 6.7% were positive by salivary PCR in the control group. About 71% were positive by RSAT in patients and 49% were positive by RSAT in controls. From 20 patients, gastric biopsy samples were taken, 11 patients were positive for H. pylori infection by gastric biopsy culture, 20 were positive by histopathological examination, and 13 were positive by rapid urea test. The salivary culture showed (100%) specificity, (38.5%) sensitivity, and (60%) accuracy. While PCR on saliva showed specificity (100%), (61.5%) sensitivity, and (75%) accuracy. RSAT showed (71.4%) specificity, 92.3% sensitivity, and 85% accuracy. Conclusion The oral cavity is an important extragastric reservoir of H. pylori; salivary PCR technique shows a much higher specificity and sensitivity than salivary culture. RSAT shows high sensitivity but with lower specificity.